Shaping competence of intercultural communication during the COVID-19 - Ayazbayeva, Saya; Mukushev, Bazarbek; Yessekeshova, Maral (International Journal of Evaluation and Research in Education (IJERE), 2025)
Shaping intercultural communication competencies during the educational process in higher education institutions is a crucial criterion for modern global education. This study considers using digital learning technologies in foreign language teaching as an efficient pedagogical strategy for developing intercultural communicative competence during the COVID-19 pandemic. The research methodology was based on a pedagogical experiment. A total of 43 students from the People’s Republic of China, Kyrgyz Republic, Republic of India, and Turkmenistan participated in three study groups. Before the experiment, the indicators of digital competence and willingness to engage in intercultural communication were low, with a high correlation between them. During the one-year academic experiment, the students studied foreign languages using digital technologies. They were involved in cultural immersion programs, master’s classes on intercultural communication, language exchange programs, virtual intercultural events, and online cultural resources. This contributed to improving intercultural communication and, at the same time, students’ digital competence.